2000
DOI: 10.1002/1096-9861(20010122)429:4<541::aid-cne3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on nerve fibers in the rhesus monkey optic nerve

Abstract: During normal aging there is a reduction in white matter volume in the cerebral hemispheres and structural abnormalities in myelin in some parts of the central nervous system, but whether nerve fibers are lost with age and whether the myelin changes are ubiquitous is not known. Studying the optic nerve, which is a circumscribed bundle of nerve fibers, offers an opportunity to gain further insight into the effects of normal aging on white matter. The present study examined the optic nerves from young (4-10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 72 publications
5
86
2
1
Order By: Relevance
“…6 Our results confirm this difference in beam thickness through the lamina cribrosa and also that beam thickness increased with increasing age in a subset of eyes. Several studies on human and primate optic nerves have found a thickening of the trabeculae of the fibrous connective tissue fascicles of the optic nerve with increasing age, [15][16][17] so it would be reasonable to find a similar increase in CBT with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…6 Our results confirm this difference in beam thickness through the lamina cribrosa and also that beam thickness increased with increasing age in a subset of eyes. Several studies on human and primate optic nerves have found a thickening of the trabeculae of the fibrous connective tissue fascicles of the optic nerve with increasing age, [15][16][17] so it would be reasonable to find a similar increase in CBT with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…At these splits, large inclusions of fluidfilled balloons or of dense inclusions were observed. These forms of myelin pathology were observed in subcortical WM of the primary visual cortex (Peters et al 2000), prefrontal cortex, and the corpus callosum (Peters and Sethares 2002), as well as the anterior commissure (Sandell and Peters 2003) and in the optic nerve (Sandell and Peters 2001). Additionally, there was significant evidence of remyelination, as reflected by the presence of redundant myelin and of increased frequency of paranodes that could reflect a shortening of internodal myelin lengths as damaged myelin was replaced by new myelin .…”
Section: Ultrastructural Observations Of Non-human Primate Cortex Witmentioning
confidence: 99%
“…Age-related changes to the optic nerve include a decrease in the number of axons [12], axonal swelling at the level of the lamina cribrosa [13], thickening of lamina cribrosa [14] and an increase in elastic fibers [15]. Harwerth et al reported a mean decline of 3 µm in retinal nerve fiber layer per decade, which represents a loss of approximately 60,000 retinal ganglion cells; furthermore, on average the retina of a 25-year-old has twice as many retinal ganglion cells as that of a 95-year-old patient [16].…”
Section: Introductionmentioning
confidence: 99%